Clinical management of lipid metabolism abnormalities induced by antipsychotics in closed psychiatric settings: challenges and integrated strategies - Jiakuan Tu; Yu Qiu; Yueting Zhang; Yang Yang; Yi Huang (Lipids in Health and Disease)
Abstract In closed psychiatric settings, antipsychotic-induced lipid metabolism abnormalities pose significant clinical challenges. Constrained by limited patient mobility, fluctuating treatment adherence, and monotonous diets, traditional management struggles to adequately balance drug side effects with patient health needs. This study presents an integrated framework involving surveillance, intervention, and interdisciplinary collaboration. It includes a comprehensive “admission-to-intervention” monitoring system, low-glycemic diet combined with portion control, symptom-specific exercise programs, and strategies to improve treatment adherence. We establish quality metrics, including 100% baseline lipid testing for new admissions and ≥ 95% timely intervention rate for abnormalities. The patient-centered model reduces cardiovascular risks, improves patient outcomes, and offers a scalable approach for metabolic health management in resource-limited environments.